2019
DOI: 10.1002/lary.28273
|View full text |Cite
|
Sign up to set email alerts
|

Cricotracheal resection for adult subglottic stenosis: Factors predicting treatment failure

Abstract: Objectives/Hypothesis Identify predictors of decannulation failure after cricotracheal resection (CTR) and thyrotracheal anastomosis (TTA) in patients with subglottic stenosis (SGS). Study Design Retrospective cohort study. Methods Charts of patients undergoing CTR and TTA for SGS at the University Health Network, Toronto, Ontario, Canada between 1988 and 2017 were reviewed. Patient, pathology, treatment, and outcome data were collected. The end points for statistical analysis were development of restenosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
4
6
0
1
Order By: Relevance
“…We consider the maximum length of a safe resection to be about 5 cm, or half of the tracheal length. Reported success rates in the literature for TR and CTR range from 65% to >95% (8)(9)(10)(11)(12)(13)(14)19,23,24). In our cohort, 33 (75%) patients did not require reoperations or postoperative interventions, which falls in the range of previous reported success rates.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…We consider the maximum length of a safe resection to be about 5 cm, or half of the tracheal length. Reported success rates in the literature for TR and CTR range from 65% to >95% (8)(9)(10)(11)(12)(13)(14)19,23,24). In our cohort, 33 (75%) patients did not require reoperations or postoperative interventions, which falls in the range of previous reported success rates.…”
Section: Discussionsupporting
confidence: 61%
“…This area has a total population of over two million people (36% of Finland's population), which further highlights how infrequently this surgery is performed. Therefore, due to their rare nature, these surgical procedures should be further centralized, as they require a multidisciplinary approach and are associated with a significant complication rate (1,3,8,(10)(11)(12)(13)(14)23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 However, in a recent study, Jethwa et al, in 2019, while studying factors predicting treatment failure in 114 patients with subglottic stenosis who underwent cricotracheal resection with stenting, concluded that longer T-tube duration was associated with higher risk of permanent tracheostomy. 14 They reported 95 per cent success (decannulation) after cricotracheal resection and thyrotracheal anastomosis. Patients had stenting for longer periods (65.1 days) if they had extensive or multiple levels of stenosis or co-morbidities that increased chances of failure.…”
Section: Duration Of Stentingmentioning
confidence: 99%